Pelatihan Keterampilan Menulis Permulaan Dengan Metode Montessori di SD Kanisius Sorowajan - Nugrahanta, Gregorius Ari; Parmadi, Eko Hari; Sekarningrum, Hilary Relita Vertikasari (Jurnal Surya Masyarakat, 2024)
The background to this community service activity began with the discovery of the low writing skills of class I students at Kanisius Sorowajan Elementary School. The aim of this activity was to improve initial writing skills by applying the Montessori method. Initial writing skills refered to a person's basic ability to organize and express ideas, ideas, or information in writing including an understanding of written structure, grammar, spelling, and the ability to convey messages clearly. This activity used the Participatory Learning and Action method which included the teacher and 17 students. The results showed, 1) an increase in children's initial writing skills scored of 77.47% which included letter writing, cohesiveness, accuracy, completeness and proportionality; 2) training using the Montessori method had a significant effect on children's initial writing skills (p < 0.05) which was included in the large effect category (r = 62.39%); and 3) the effectiveness of implementing the Montessori method was in the large category (n-gain score = 89.24%).